Modification of the screw hole structures to improve the fatigue strength of locking plates. (May 2018) - Lin, Chen-Huei; Chao, Ching-Kong; Ho, Yu-Jou; Lin, Jinn
Abstract: Background: The fatigue fracture of locking plates can substantially threaten fracture treatment results. In the present study, three measures for modifying the screw hole structures of plates were implemented to improve their fatigue strength. Materials: Custom-made identical titanium locking plates, except the screw hole configurations, were tested using four-point bending load. The three measures were partial removal of screw threads on the tension side of the plates, reduction of screw hole size, and modification of the thread radii. There were six types of plates: control (Type I), half of the threads removed (Type II) or one-third of the threads (Type III), smaller screw holes (Type IV), and increase of the thread root radii (Type V) or crest radii (Type VI). Findings: Compared with the control, Types II and III significantly improved the fatigue strength (14.5 and 10.1 times, respectively). Decreasing the size of the screw hole (Type IV) also yielded a higher fatigue strength (17.6%). Type VI significantly improved the fatigue strength (9.8 times). However, Type V decreased the fatigue strength (14%). For cyclic stiffness, Type IV was significantly higher than other types statistically. Failure analyses showed typical fatigue fracture in all plates and the cracks were always initiated at the thread crest. Interpretations: The fatigue strength of titanium locking plates can be significantly improved by structural changes in the screw holes. Removing the threads of the plates and increasing the crest radii of the threads were more effective measures than decreasing the size of the screw holes. Highlights: Fatigue strength of titanium locking plates can be improved. Removing threads and increasing crest radii can increase fatigue strength. Decreasing the screw hole size can also increase strength, but not significantly.